2014
DOI: 10.1002/2013jd021252
|View full text |Cite
|
Sign up to set email alerts
|

Circulation changes in the stratosphere and mesosphere during the stratospheric sudden warming event in January 2009

Abstract: In this study, general circulation changes are investigated during the stratospheric sudden warming event in January 2009 by the use of Aura Earth Observing System Microwave Limb Sounder observations to show dynamical coupling of stratosphere and mesosphere. It is revealed that the reversal from westerly winds to easterly winds occurred earlier in the mesosphere in comparison with the stratopause level and suggested that the earlier reversal in the mesosphere may be caused by large‐scale waves formed in the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 19 publications
5
50
0
Order By: Relevance
“…In a model study, Siskind et al (2010) discussed the possible in situ generation of SPWs in the mesosphere via a combination of forcing from below and in situ instability. The in situ generation of SPWs by instabilities in the lower mesosphere was confirmed by Iida et al (2014) using satellite observations.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…In a model study, Siskind et al (2010) discussed the possible in situ generation of SPWs in the mesosphere via a combination of forcing from below and in situ instability. The in situ generation of SPWs by instabilities in the lower mesosphere was confirmed by Iida et al (2014) using satellite observations.…”
Section: Introductionmentioning
confidence: 69%
“…This indicates in situ generation of SPWs by instabilities (Siskind et al, 2010). Furthermore, similarly to Iida et al (2014) the stratospheric PNJ and the mesospheric subtropical jet were intensified, conceivably bringing about instabilities in the mesosphere, and hence the possibility of the generation of SPWs in the mesosphere.…”
Section: Why Does the Spw 2 Dominate In Period Ii?mentioning
confidence: 83%
See 1 more Smart Citation
“…Iida et al (2014) showed instabilities forming SPWs might be brought about by an intensification of the PNJ in the stratosphere and the subtropical westerly jet in the mesosphere which is the case in Period I (cf. Fig.…”
mentioning
confidence: 95%
“…It has been suggested that the MASTJ, related to the solar cycle, modulates stratospheric mean meridional circulation, which further influences convective activity in the tropical troposphere (Kodera, 2004;Kodera and Shibata, 2006). On the other hand, it has been pointed out that the MASTJ may be important for the formation of a kind of dynamical instability in the extratropical mesosphere (Iida et al, 2014).…”
Section: Introductionmentioning
confidence: 99%